2008
DOI: 10.1016/j.neuroimage.2008.06.043
|View full text |Cite
|
Sign up to set email alerts
|

Morphological priming in overt language production: Electrophysiological evidence from Dutch

Abstract: a b s t r a c t a r t i c l e i n f oThe present study investigated morphological priming in Dutch and its time course in overt speech production using a long-lag priming paradigm. Prime words were compounds that were morphologically related to a picture name (e.g. the word jaszak, 'coat pocket' was used for a picture of a coat; Dutch jas) or form-related monomorphemic words (e.g. jasmijn, 'jasmine'). The morphologically related compounds could be semantically transparent (e.g. eksternest, 'magpie nest') or op… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

22
115
1
2

Year Published

2010
2010
2023
2023

Publication Types

Select...
3
2
1

Relationship

1
5

Authors

Journals

citations
Cited by 113 publications
(140 citation statements)
references
References 71 publications
22
115
1
2
Order By: Relevance
“…Only a few studies used overt production (immediate picture naming), with MEG (Levelt, Praamstra, Meyer, Helenius, & Salmelin, 1998;Maess, Friederici, Damian, Meyer, & Levelt, 2002) or with EEG (Eulitz, Hauk, & Cohen, 2000;Koester & Schiller, 2008;Strijkers et al, 2009).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Only a few studies used overt production (immediate picture naming), with MEG (Levelt, Praamstra, Meyer, Helenius, & Salmelin, 1998;Maess, Friederici, Damian, Meyer, & Levelt, 2002) or with EEG (Eulitz, Hauk, & Cohen, 2000;Koester & Schiller, 2008;Strijkers et al, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…It should be emphasised however that even ERP studies using an overt production paradigm and analysing epochs relative to picture onset might be missing these encoding processes, especially when the response onset exceeds the time-window considered in the analyses. In fact, in these overt production studies stimulus-aligned epochs have been analysed with a time-period varying from 500 ms (Maess et al, 2002) to 700 ms after picture onset (Koester & Schiller, 2008) in order to avoid artefacts due to motor execution. For instance, in the study by Strijkers et al (2009) the time-window of the analysed ERP was chosen in order to stop 100 ms before the fastest response latency.…”
Section: Introductionmentioning
confidence: 99%
“…Thus, very frequently used compounds (e.g., 'airport') and opaque ones (e.g., 'butterfly') are supposedly stored in their full form whereas less frequent compounds would be decomposed and their constituents' meaning needs to be combined. In a previous study using morphological priming in overt speech with existing compounds (Koester and Schiller, 2008) full-parsing and dual-route models (Badecker, 2001;Levelt et al, 1999;Taft, 2004) were proposed to account for the data, suggesting that morphemes might be planning units in language production (Roelofs, 2002). In the present work, novel compound words were formed by combining two existing morphemes (e.g.…”
Section: Sessionmentioning
confidence: 68%
“…In contrast, relatively little is known about the neuro-cognitive correlates of compound production. In Koester and Schiller (2008) and Lensink et al (2014), using the previously mentioned morphological priming task, the N400 amplitudes were reduced for the morphologically related condition compared to the unrelated one. This corresponds to the language comprehension literature, where evidence has been found that N400 amplitudes are sensitive to morphological processing (e.g., McKinnon et al, 2003).…”
Section: Introductionmentioning
confidence: 90%
See 1 more Smart Citation